The efficacy of nisin against Listeria monocytogenes on cold-smoked salmon at natural contamination levels is concentration-dependent and varies by serotype - Chen, Ruixi; Skeens, Jordan William; Wiedmann, Martin; Guariglia-Oropeza, Veronica (Frontiers in Microbiology, 2022)
Cold-smoked salmon is a ready-to-eat food product capable of supporting Listeria monocytogenes growth at refrigeration temperatures. While the FDA-approved antimicrobial nisin can be used to mitigate L. monocytogenes contamination, stresses associated with cold-smoked salmon and the associated processing environments may reduce nisin efficacy. A previous study in our laboratory showed that, at high inoculation levels, pre-exposure of L. monocytogenes to sublethal concentrations of quaternary ammonium compounds had an overall detrimental effect on nisin efficacy. The objective of this study was to investigate the impact of nisin concentration and storage temperature on nisin efficacy against L. monocytogenes inoculated on salmon at natural contamination levels. Three L. monocytogenes strains were pre-grown in the presence of sublethal levels of benzalkonium chloride prior to inoculation at ~100 CFU/g on salmon slices that were pre-treated with either 0, 25, or 250 ppm nisin, followed by vacuum-packing and incubation at 4 or 7ºC for up to 30 days. L. monocytogenes was enumerated on days 1, 15, and 30 using direct plating and/or most probable number methods. A hurdle model was constructed to describe the odds of complete elimination of L. monocytogenes on salmon and the level of L. monocytogenes when complete elimination was not achieved. Our data showed that (i) nisin efficacy (defined as L. monocytogenes reduction relative to the untreated control) was concentration-dependent with increased efficacy at 250 ppm nisin, and that (ii) 250 ppm nisin treatments led to a reduction in L. monocytogenes prevalence, independent of storage temperature and serotype; this effect of nisin could only be identified since low inoculation levels were used. While lower storage temperatures (i.e., 4ºC) yielded lowered absolute L. monocytogenes counts on days 15 and 30 (as compared to 7ºC), nisin efficacy did not differ between these two temperatures. Finally, the serotype 1/2b strain was found to be more susceptible to nisin compared with serotype 1/2a and 4b strains on samples incubated at 7ºC or treated with 25 ppm nisin. This variation of nisin susceptibility across serotypes, which is affected by both the storage temperature and nisin concentration, needs to be considered while evaluating the efficacy of nisin.